A preparation method of β-solidified γ-TiAl alloy with dual-state structure having layered distribution characteristics
By using the composite method of creep deformation and short-time heat treatment in β-solidified γ-TiAl alloy, a two-state structure with layered distribution characteristics is formed, which solves the problem of insufficient creep resistance of the alloy and improves the high-temperature service capacity and production efficiency .
Patent Information
- Application Number
- CN202311155126.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-09-07
AI Technical Summary
The creep resistance of β-solidified γ-TiAl alloys is insufficient, which limits its serviceability at high temperatures. Existing processing methods such as additive manufacturing, isometric angle extrusion and hot pressing sintering have high costs, limited size or ease of use. Impurities introduced.
The vermismorphing technology under medium temperature, constant load and slow speed conditions combined with short-term heat treatment is used to gradually decompose and reconstruct the distribution of α2/γ sheet layer clusters to form a two-state structure with layered distribution characteristics.
The creep resistance of β-solidified γ-TiAl alloy is improved, production costs are reduced, alloy cracking is avoided, and higher controllability and stability are achieved, and the service temperature limit of the alloy is extended.
Smart Images

Figure CN117165883B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of beta-solidified gamma-TiAl alloys, in particular to a method for preparing a beta-solidified gamma-TiAl alloy with a dual-state structure having a layered distribution characteristic. Background Art
[0002] The rapid development of the aviation industry has put forward higher requirements on the thrust-to-weight ratio, service life and service temperature limit of aircraft engines. In addition to structural design and optimization, the development of new high-temperature lightweight structural materials has become a key factor in achieving engine lightweighting, high carrying efficiency and low NO x The main way to reduce emissions. The widely used nickel-based high-temperature alloys and high-temperature titanium alloys at this stage have approached their respective service limits. Therefore, it is urgent to develop a new type of lightweight, high-strength, and high-temperature resistant structural material. In recent decades, due to its excellent properties such as low density, high specific strength and specific modulus, and good oxidation resistance, TiAl alloys have attracted widespread attention from the material science and engineering communities at home and abroad. At present, TiAl alloys have been successfully applied in aeroengines and other fields. In 2006, the Ti-48Al-2Cr-2Nb alloy low-pressure turbine blades developed by GE were used in the GEnx-1B engine of the Boeing 787 aircraft. In 2014, the new β-solidified γ-TiAl alloy low-pressure turbine blades made their first flight on the Airbus A320neo aircraft. At present, β-solidified γ-TiAl alloy has become a hot research direction in the field of TiAl alloys due to its advantages such as uniform solidification structure and strong high-temperature deformation ability.
[0003] TiAl alloys contain four typical microstructures, among which the dual-state structure is mainly composed of uniformly distributed α2 / γ lamellar clusters and γ equiaxed crystals. TiAl alloys with dual-state structures often show good plasticity, but insufficient creep resistance. It is well known that insufficient creep resistance will greatly limit the service temperature limit of TiAl alloys. Therefore, it is necessary to improve the creep resistance. In order to improve the creep resistance of TiAl alloys, most precipitate particles such as carbides, silicides and yttrium oxide are introduced into the alloy. However, the uneven distribution of these precipitate particles will lead to unstable strengthening effect. Recently, the concept of "heterostructure" has been gradually accepted by many scholars. By constructing heterostructures, back stress strengthening can be exerted, thereby greatly improving the performance of alloys. Common heterostructures are layered heterostructures. At present, the ways to obtain heterostructures mainly include additive manufacturing, equal-channel angular extrusion, rolling, hot pressing and sintering. However, the above methods all have their own disadvantages: (1) Additive manufacturing: expensive, limited alloy component size, and extremely high requirements on the quality of the original powder; (2) Equal channel angular pressing and rolling: for brittle TiAl alloys, the processing window is narrow and prone to cracking; (3) Hot pressing sintering: other impurities are easily introduced during the powder mixing process, which reduces the performance stability of the final alloy. Therefore, it is necessary to seek a new method suitable for brittle TiAl alloys to obtain layered heterogeneous structures.
[0004] Based on the above analysis, in order to improve the creep resistance of β-solidifying γ-TiAl alloy and promote its service at higher temperatures, it is necessary to introduce a heterogeneous structure into the alloy. Summary of the invention
[0005] The present invention provides a method for preparing a β-solidified γ-TiAl alloy with a dual-state structure having a layered distribution characteristic in order to solve the technical problem that the creep resistance of the TiAl alloy is insufficient under the condition of ensuring room temperature plasticity.
[0006] The present invention proposes a composite method of forming technology (creep forming) under medium temperature, constant load and slow speed conditions combined with subsequent short-time heat treatment to obtain a dual-state structure with layered distribution characteristics. First, the dynamic recrystallization mechanism is activated by creep forming, so that the original lamellar clusters are gradually decomposed and rotated to form preliminary lamellar distribution characteristics. Then, a suitable short-time heat treatment system is applied to reconstruct the distribution of lamellar clusters and equiaxed crystals, thereby forming the final dual-state structure with a heterogeneous structure with layered distribution characteristics.
[0007] A method for preparing a β-solidified γ-TiAl alloy having a dual-state structure with a layered distribution characteristic, the method specifically comprising the following steps:
[0008] 1. Weigh pure Ti rods, sponge Ti particles, high-purity Al blocks, Al-Nb master alloy particles, Al-Mo master alloy particles and pure B powder according to the atomic percentage composition of: Al is 42% to 45%, Nb is 3% to 6%, Mo is 0.5% to 2%, B is ≤ 0.3% and the balance is Ti; ultrasonically clean the weighed metal raw materials (including pure Ti rods, sponge Ti particles, high-purity Al blocks, Al-Nb master alloy particles and Al-Mo master alloy particles) and put them into a drying oven to fully dry;
[0009] The treated Al-Nb master alloy particles and Al-Mo master alloy particles are uniformly mixed to obtain mixed particles, and the pure B powder is wrapped with Al foil;
[0010] 2. Smelting: ① Place the metal raw materials processed in step 1 into a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace: Sponge Ti particles are spread on the bottom of the crucible, pure Ti rods are evenly erected around the inner wall of the crucible, mixed particles formed by Al-Nb master alloy particles and Al-Mo master alloy particles are spread on the sponge titanium, pure Al blocks are placed on the mixed particles, pure B powder wrapped in Al foil is placed in the secondary feeding hopper, and the furnace door is closed;
[0011] ② Vacuuming treatment: When the vacuum degree is lower than 5Pa, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa; then perform secondary vacuuming. When the vacuum degree is lower than 5Pa again, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa;
[0012] ③ Heating and smelting: First, control the heating power to 20-40kW; when the pure Al block is melted, increase the power to 45-55kW and keep it for 5-10min; increase the power to 65-75kW, and when all the metal raw materials are completely melted to form a uniform melt, reduce the power to 20-35kW, control the melt level to maintain a stable level, then pour the secondary feeding hopper and add pure B powder wrapped in Al foil to the melt; increase the power to 70-85kW, maintain the heating power and continue heating for 6-10min, and perform electromagnetic stirring at the same time to obtain an alloy melt;
[0013] ④ Reduce the power to 0, and pour the alloy melt into the preheated stainless steel mold within 2 seconds;
[0014] ⑤ When the alloy melt solidifies to form an alloy ingot and cools to room temperature, high-purity argon gas is filled into the furnace, the furnace door is opened, and the mold and the alloy ingot are taken out;
[0015] 3. Annealing treatment: placing the alloy ingot obtained in step 2 into a heat treatment furnace, heating it up with the furnace, keeping it at 940-1000°C for 25-38h, and then cooling it to room temperature with the furnace to obtain a β-solidified γ-TiAl alloy ingot;
[0016] 4. Creep forming: cut a number of cylinders from the β-solidifying γ-TiAl alloy ingot obtained in step 3, perform surface grinding, ultrasonic cleaning for about 15 to 20 minutes, and obtain a cylindrical sample; place the cylindrical sample in the exact center between the upper and lower pressure heads of the electronic creep endurance tester, and fix three K-type thermocouples on the upper pressure head, the lower pressure head and the vicinity of the cylindrical sample, respectively, to perform real-time temperature monitoring and temperature correction; apply a preload to fix the cylindrical sample; close the insulation furnace, heat it at a rate of 18 to 26°C / min, and when the forming temperature reaches 860 to 960°C, keep it warm for 20 to 40 minutes; then, load it at a rate of 100 to 180N / s to a forming load of 12000 to 20000N, maintain the load for 3 to 5.5 hours, and control the total compressive strain to be 70% to 80%; remove the load, then cool it to room temperature with the furnace, and take out the creep-formed sample, i.e., the β-solidifying γ-TiAl alloy sample;
[0017] 5. Determine the heat treatment temperature: Use differential scanning calorimetry to analyze the β-solidified γ-TiAl alloy sample obtained in step 4 and measure the α phase transformation temperature T α .
[0018] 6. Heat treatment: The β-solidified γ-TiAl alloy sample after creep forming in step 4 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised uniformly at a rate of 12 to 18 °C / min to 500 to 550 °C, and maintained for 2 to 8 minutes; then the temperature is raised uniformly at a rate of 12 to 16 °C / min to the target temperature (T α -30)~(T α -10)℃, keep for 10-30min; and cool to room temperature along with the furnace to obtain the final sample, that is, the β-solidifying γ-TiAl alloy with a dual-state structure with layered distribution characteristics, and the preparation is completed.
[0019] The β-solidified γ-TiAl alloy with layered heterogeneous structure provided by the present invention has good creep resistance. Compared with additive manufacturing or conventional thermomechanical processing, the composite method of creep forming combined with short-time heat treatment can not only achieve the desired effect, but also reduce the production cost. By introducing a layered heterogeneous structure into the β-solidified γ-TiAl alloy through this method, the creep resistance of the alloy can be improved, which is extremely important for the alloy to be able to serve at higher temperatures.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention ingeniously utilizes creep forming method to produce a large number of recrystallized grains in the cast β-solidified γ-TiAl alloy, which not only decomposes the lamellar clusters, but also rotates the lamellar clusters to form a layered distribution feature. This method makes up for the disadvantages of other traditional thermomechanical processing methods, improves controllability, and avoids alloy cracking.
[0022] (2) The present invention changes the distribution configuration of α2 / γ lamellar clusters and γ equiaxed crystals by performing a short-time heat treatment on the β-solidified γ-TiAl alloy after creep forming in the (α+γ) dual phase region below the α phase transformation temperature, and successfully obtains a dual-state structure with lamellar distribution characteristics. On the one hand, the alloy contains trace B elements, which greatly refines the lamellar cluster size of the cast alloy, and this alloy has certain heterogeneous structural characteristics after creep forming. On the other hand, heat treatment in the (α+γ) dual phase region can prevent all γ grains from being transformed into α grains. In other words, short-time heat treatment in this temperature range can only ensure that part of the γ grains are transformed into α grains, and these α grains will eventually transform into (α2+γ) lamellar clusters after cooling. Crucially, there are heterogeneous structural characteristics after creep forming, and the γ grains near the residual lamellar clusters are more likely to transform into α grains, while the γ grains far away from the residual lamellar clusters have not yet transformed and remain. Therefore, a dual-state structure with a layered distribution characteristic of (α2+γ) lamellar clusters / equiaxed γ crystal layers alternately arranged is finally formed. The heat treatment in the present invention is single-step and short-term, which is convenient for practical operation. At the same time, the cooling method is furnace cooling, which avoids cracking of the alloy due to too fast cooling rate. In addition, short-term heat treatment can avoid excessive growth of grains during high temperature insulation, and too large grains are unfavorable for room temperature plasticity.
[0023] The method proposed by the present invention to obtain a layered heterogeneous structure by creep forming combined with heat treatment has strong operability, simple process, short production cycle, and can improve the creep resistance of β-solidifying γ-TiAl alloy. This has far-reaching significance for improving the service temperature limit of β-solidifying γ-TiAl alloy.
[0024] The method of the invention is used for preparing a beta-solidified gamma-TiAl alloy with a dual-state structure having a layered distribution characteristic. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a microstructure photograph of the β-solidified γ-TiAl alloy ingot after annealing in step 3 of Example 1; Figure 1 (a) is an optical microscope image, Figure 1 (b) is a scanning electron microscope image. Figure 1 (c) Yes Figure 1 (b) Local magnified image of the white box area;
[0026] Figure 2 This is a microstructure photograph of the β-solidified γ-TiAl alloy sample after creep forming in step 4 of Example 1; Figure 2 (a) is a scanning electron microscope image. Figure 2 (b) Yes Figure 2 (a) Local magnified image of the white box area;
[0027] Figure 3 This is a scanning electron microscope image of the microstructure of the β-solidified γ-TiAl alloy after heat treatment in step 6 of Example 1; Figure 3 (a) and Figure 3 (b) are the microstructure images of two random locations. Figure 3 (c) Yes Figure 3 (b) A local enlarged image of the white box area. DETAILED DESCRIPTION
[0028] Specific implementation method 1: This implementation method is a preparation method of a β-solidified γ-TiAl alloy with a dual-state structure with layered distribution characteristics, which is specifically carried out in the following steps:
[0029] 1. Weigh pure Ti rods, Ti sponge particles, high-purity Al blocks, Al-Nb master alloy particles, Al-Mo master alloy particles and pure B powder according to the atomic percentage composition of: Al 42% to 45%, Nb 3% to 6%, Mo 0.5% to 2%, B ≤ 0.3% and the balance Ti; ultrasonically clean the weighed metal raw materials and put them into a drying oven to fully dry;
[0030] The treated Al-Nb master alloy particles and Al-Mo master alloy particles are uniformly mixed to obtain mixed particles, and the pure B powder is wrapped with Al foil;
[0031] 2. Smelting: ① Place the metal raw materials processed in step 1 into a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace: Sponge Ti particles are spread on the bottom of the crucible, pure Ti rods are evenly erected around the inner wall of the crucible, mixed particles formed by Al-Nb master alloy particles and Al-Mo master alloy particles are spread on the sponge titanium, pure Al blocks are placed on the mixed particles, pure B powder wrapped in Al foil is placed in the secondary feeding hopper, and the furnace door is closed;
[0032] ② Vacuuming treatment: When the vacuum degree is lower than 5Pa, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa; then perform secondary vacuuming. When the vacuum degree is lower than 5Pa again, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa;
[0033] ③ Heating and smelting: First, control the heating power to 20-40kW; when the pure Al block is melted, increase the power to 45-55kW and keep it for 5-10min; increase the power to 65-75kW, and when all the metal raw materials are completely melted to form a uniform melt, reduce the power to 20-35kW, control the melt level to maintain a stable level, then pour the secondary feeding hopper and add pure B powder wrapped in Al foil to the melt; increase the power to 70-85kW, maintain the heating power and continue heating for 6-10min, and perform electromagnetic stirring at the same time to obtain an alloy melt;
[0034] ④ Reduce the power to 0, and pour the alloy melt into the preheated stainless steel mold within 2 seconds;
[0035] ⑤ When the alloy melt solidifies to form an alloy ingot and cools to room temperature, high-purity argon gas is filled into the furnace, the furnace door is opened, and the mold and the alloy ingot are taken out;
[0036] 3. Annealing treatment: placing the alloy ingot obtained in step 2 into a heat treatment furnace, heating it up with the furnace, keeping it at 940-1000°C for 25-38h, and then cooling it to room temperature with the furnace to obtain a β-solidified γ-TiAl alloy ingot;
[0037] 4. Creep forming: cut a number of cylinders from the β-solidifying γ-TiAl alloy ingot obtained in step 3, perform surface grinding, ultrasonic cleaning for about 15 to 20 minutes, and obtain a cylindrical sample; place the cylindrical sample in the exact center between the upper and lower pressure heads of the electronic creep endurance tester, and fix three K-type thermocouples on the upper pressure head, the lower pressure head and the vicinity of the cylindrical sample, respectively, to perform real-time temperature monitoring and temperature correction; apply a preload to fix the cylindrical sample; close the insulation furnace, heat it at a rate of 18 to 26°C / min, and when the forming temperature reaches 860 to 960°C, keep it warm for 20 to 40 minutes; then, load it at a rate of 100 to 180N / s to a forming load of 12000 to 20000N, maintain the load for 3 to 5.5 hours, and control the total compressive strain to be 70% to 80%; remove the load, then cool it to room temperature with the furnace, and take out the creep-formed sample, i.e., the β-solidifying γ-TiAl alloy sample;
[0038] 5. Determine the heat treatment temperature: Use differential scanning calorimetry to analyze the β-solidified γ-TiAl alloy sample obtained in step 4 and measure the α phase transformation temperature T α .
[0039] 6. Heat treatment: The β-solidified γ-TiAl alloy sample after creep forming in step 4 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised uniformly at a rate of 12 to 18 °C / min to 500 to 550 °C, and maintained for 2 to 8 minutes; then the temperature is raised uniformly at a rate of 12 to 16 °C / min to the target temperature (T α-30)~(T α -10)℃, keep for 10-30min; and cool to room temperature along with the furnace to obtain the final sample, that is, the β-solidifying γ-TiAl alloy with a dual-state structure with layered distribution characteristics, and the preparation is completed.
[0040] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that anhydrous ethanol is used for ultrasonic cleaning in step 1. The rest is the same as specific implementation method 1.
[0041] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the purity of the pure Ti rod in step 1 is greater than 99.9%, the purity of the sponge Ti particles is greater than 99.9%, the purity of the high-purity Al block is greater than 99.9%, the Nb content in the Al-Nb master alloy particles is 53.7wt.%, the Mo content in the Al-Mo master alloy particles is 50.5wt.%, and the purity of the pure B powder is greater than 99.9%. Others are the same as specific embodiment 1 or 2.
[0042] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: 4-6% of the mass of Al element is added during weighing in step 1 to compensate for the volatilization of Al element during the smelting process. The rest is the same as specific embodiments 1 to 3.
[0043] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that: in step 4, 200# to 3000# sandpaper is used for surface polishing. The rest is the same as specific implementation methods 1 to 4.
[0044] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the material of the pressure head in step 4 is a nickel-based high-temperature alloy. The rest is the same as specific implementation methods 1 to 5.
[0045] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: in step 4, the temperature fluctuation range of the forming process is controlled to be -1 to 1° C. The rest is the same as specific embodiments 1 to 6.
[0046] Specific implementation example 8: This implementation example is different from specific implementation examples 1 to 7 in that the preload applied in step 4 is 450 to 900 N. The rest is the same as specific implementation examples 1 to 7.
[0047] Specific implementation method 9: This implementation method is different from specific implementation methods 1 to 8 in that the size of the cylinder in step 4 is Φ8mm×12mm. The rest is the same as specific implementation methods 1 to 8.
[0048] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that anhydrous ethanol is used for ultrasonic cleaning in step 4. The rest is the same as specific embodiments 1 to 9.
[0049] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.
[0050] Embodiment 1:
[0051] The chemical composition of the β-solidifying γ-TiAl alloy of this embodiment is Ti-43.5Al-4Nb-1Mo-0.1B (atomic percentage).
[0052] A method for preparing a β-solidified γ-TiAl alloy having a dual-state structure with a layered distribution characteristic is specifically carried out in the following steps:
[0053] 1. According to the atomic percentage composition of 43.5% Al, 4% Nb, 1% Mo, 0.1% B and the balance Ti, pure Ti rods (purity>99.9%), sponge Ti particles (purity>99.9%), high-purity Al blocks (purity>99.9%), Al-Nb master alloy particles (Nb content of 53.7wt.%), Al-Mo master alloy particles (Mo content of 50.5wt.%) and pure B powder (purity>99.9%) are weighed. Since the smelting process is carried out in a vacuum environment, more Al elements need to be added to compensate for the volatilization of Al elements. The compensated Al element content is about 4% to 6% of the nominal Al content; the weighed metal raw materials are ultrasonically cleaned for 10 minutes with anhydrous ethanol and placed in a drying oven for full drying;
[0054] The treated Al-Nb master alloy particles and Al-Mo master alloy particles are uniformly mixed to obtain mixed particles, and the pure B powder is wrapped with Al foil;
[0055] 2. Smelting: ① Place the metal raw materials processed in step 1 into a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace: Sponge Ti particles are spread on the bottom of the crucible, pure Ti rods are evenly erected around the inner wall of the crucible, mixed particles formed by Al-Nb master alloy particles and Al-Mo master alloy particles are spread on the sponge titanium, pure Al blocks are placed on the mixed particles, pure B powder wrapped in Al foil is placed in the secondary feeding hopper, and the furnace door is closed;
[0056] ② Vacuuming treatment: When the vacuum degree is lower than 5Pa, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa; then perform secondary vacuuming. When the vacuum degree is lower than 5Pa again, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa;
[0057] ③ Heating and smelting: First, control the heating power to 24kW; when the pure Al block is melted, increase the power to 48kW and keep it for 5min; increase the power to 68kW, and when all the metal raw materials are completely melted to form a uniform melt, reduce the power to 22kW, control the melt level to maintain a stable level, then pour the secondary feeding hopper and add pure B powder wrapped in Al foil to the melt; increase the power to 78kW, maintain the heating power and continue heating for 8min, while performing electromagnetic stirring to obtain an alloy melt;
[0058] ④ Reduce the power to 0, and pour the alloy melt into the preheated stainless steel mold within 2 seconds;
[0059] ⑤ When the alloy melt solidifies to form an alloy ingot and cools to room temperature, high-purity argon gas is filled into the furnace, the furnace door is opened, and the mold and the alloy ingot are taken out;
[0060] 3. Annealing treatment: placing the alloy ingot obtained in step 2 into a heat treatment furnace, heating it up with the furnace, keeping it at 950°C for 36 hours, and then cooling it to room temperature with the furnace to obtain a β-solidified γ-TiAl alloy ingot;
[0061] 4. Creep forming: Cut a number of cylinders from the β-solidified γ-TiAl alloy ingot obtained in step 3. The cylinder size is 8mm×12mm. Use 200#~3000# sandpaper for surface grinding and use anhydrous ethanol ultrasonic cleaning for 10 minutes to obtain a cylindrical sample. Put the cylindrical sample in the center between the upper and lower pressure heads of an electronic creep endurance tester. The pressure head material is a nickel-based high-temperature alloy. Fix three K-type thermocouples on the upper pressure head, the lower pressure head and the vicinity of the cylindrical sample for real-time testing. Temperature monitoring and temperature correction are performed to control the temperature fluctuation range during the forming process to -1 to 1°C; a preload of 700N is applied to fix the cylindrical sample; the holding furnace is closed, and the temperature is increased at a rate of 20°C / min. When the forming temperature reaches 950°C, the temperature is kept for 30 minutes; then, the forming load is loaded to 16590N at a rate of 120N / s, and the load is maintained for 4 hours, and the total compressive strain is controlled to be 75%; the load is removed, and then the sample is cooled to room temperature with the furnace, and the creep-formed sample, i.e., the β-solidified γ-TiAl alloy sample, is taken out;
[0062] 5. Determine the heat treatment temperature: Use differential scanning calorimetry to analyze the β-solidified γ-TiAl alloy sample obtained in step 4 and measure the α phase transformation temperature T α It is 1293℃.
[0063] 6. Heat treatment: The β-solidifying γ-TiAl alloy sample after creep forming in step 4 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised to 520°C at a uniform rate of 16°C / min and maintained for 4 minutes; the temperature is then raised to the target temperature of 1280°C at a uniform rate of 13°C / min and maintained for 15 minutes; the sample is cooled to room temperature in the furnace to obtain the final sample, which is a β-solidifying γ-TiAl alloy with a dual-state structure with layered distribution characteristics, and the preparation is completed.
[0064] Figure 1 This is a microstructure photograph of the β-solidified γ-TiAl alloy ingot after annealing in step 3 of Example 1; Figure 1 (a) is an optical microscope image, Figure 1 (b) is a scanning electron microscope image. Figure 1 (c) Yes Figure 1 (b) A local magnified image of the white box area. The cast Ti-43.5Al-4Nb-1Mo-0.1B alloy exhibits a typical near-lamellar structure, in which the α2 / γ lamellar clusters and γ equiaxed grains are relatively uniformly distributed. According to the test, the creep strain of the alloy in this state after 50h of compression creep at 800℃ and 300MPa is about 29.5%, which means that the creep resistance is poor.
[0065] Figure 2 This is a microstructure photograph of the β-solidified γ-TiAl alloy sample after creep forming in step 4 of Example 1; Figure 2 (a) is a scanning electron microscope image. Figure 2 (b) Yes Figure 2 (a) A local magnified image of the white box area. Figure 2 It can be seen from (a) that after creep deformation, the alloy exhibits a nearly lamellar distribution feature (lamellar clusters / equiaxed crystals are distributed alternately). Figure 2 (b) It can be seen that the equiaxed crystals are mainly recrystallized grains. The lamellar clusters are decomposed and gradually rotated, and the orientations of several lamellar clusters tend to be consistent.
[0066] Figure 3 This is a scanning electron microscope image of the microstructure of the β-solidified γ-TiAl alloy after heat treatment in step 6 of Example 1; Figure 3 (a) and Figure 3 (b) are the microstructure images of two random locations. Figure 3 (c) Yes Figure 3(b) Local magnified image of the white box area. Obviously, the alloy exhibits a dual-state structure with lamellar distribution characteristics, in which lamellar clusters and equiaxed crystal layers are arranged alternately. In contrast, the thickness of the lamellar clusters is greater than that of the equiaxed crystal layers. More lamellar clusters are conducive to creep resistance, while equiaxed crystals ensure that the alloy has good plasticity. According to the test, the creep strain of the alloy in this state after 50h of compression creep at 800℃ and 300MPa is about 15.6%, which means that compared with the cast alloy, the creep resistance of the alloy is improved after creep forming and short-time heat treatment. This also proves the effectiveness of introducing lamellar heterogeneous structures to improve the creep resistance of β-solidifying γ-TiAl alloys.
[0067] According to the above embodiments, the present invention successfully obtains a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic by using a composite method of creep forming under low strain rate and low forming load conditions combined with subsequent short-time heat treatment, and improves the creep resistance of this alloy.
Claims
1. A method for preparing a β-solidified γ-TiAl alloy having a dual-state structure with a layered distribution characteristic, characterized in that The method is specifically carried out in the following steps:
1. According to the atomic percentage composition of Al 42% to 45%, Nb 3% to 6%, Mo 0.5% to 2%, B ≤ 0.3% and the balance Ti, weigh pure Ti rods, sponge Ti particles, high-purity Al blocks, Al-Nb master alloy particles, Al-Mo master alloy particles and pure B powder; ultrasonically clean the weighed metal raw materials and put them into a drying oven to fully dry; The treated Al-Nb master alloy particles and Al-Mo master alloy particles are uniformly mixed to obtain mixed particles, and the pure B powder is wrapped with Al foil; 2. Smelting: ① Place the metal raw materials processed in step 1 into a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace: Sponge Ti particles are spread on the bottom of the crucible, pure Ti rods are evenly erected around the inner wall of the crucible, mixed particles formed by Al-Nb master alloy particles and Al-Mo master alloy particles are spread on the sponge Ti particles, high-purity Al blocks are placed on the mixed particles, pure B powder wrapped in Al foil is placed in the secondary feeding hopper, and the furnace door is closed; ② Vacuuming treatment: When the vacuum degree is lower than 5Pa, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa; then perform secondary vacuuming. When the vacuum degree is lower than 5Pa again, high-purity argon gas is filled into the furnace until the pressure in the furnace is 800Pa; ③ Heating and smelting: First, control the heating power to 20~40 kW; when the high-purity Al block is melted, increase the power to 45~55kW and maintain it for 5~10 minutes; increase the power to 65~75 kW, and when all the metal raw materials are completely melted to form a uniform melt, reduce the power to 20~35 kW, control the melt level to maintain a stable level, then pour the secondary feeding hopper and add pure B powder wrapped in Al foil to the melt; increase the power to 70~85kW, maintain the heating power and continue heating for 6~10 minutes, while performing electromagnetic stirring to obtain an alloy melt; ④ Reduce the power to 0, and pour the alloy melt into the preheated stainless steel mold within 2 seconds; ⑤ When the alloy melt solidifies to form an alloy ingot and cools to room temperature, high-purity argon gas is filled into the furnace, the furnace door is opened, and the mold and the alloy ingot are taken out; 3. Annealing treatment: placing the alloy ingot obtained in step 2 into a heat treatment furnace, heating it up with the furnace, keeping it at 940-1000°C for 25-38h, and then cooling it to room temperature with the furnace to obtain a β-solidified γ-TiAl alloy ingot; 4. Creep forming: cut several cylinders from the β-solidifying γ-TiAl alloy ingot obtained in step 3, perform surface grinding, ultrasonic cleaning for 15-20 min, and obtain cylindrical samples; place the cylindrical samples in the exact center between the upper and lower pressure heads of the electronic creep endurance testing machine, and fix three K-type thermocouples on the upper pressure head, the lower pressure head and the vicinity of the cylindrical samples, respectively, to perform real-time temperature monitoring and temperature correction; apply a preload to fix the cylindrical samples; close the insulation furnace, heat up at a rate of 18-26 ℃ / min, and when the forming temperature reaches 860-960 ℃, keep warm for 20-40 min; then, load at a rate of 100-180 N / s to a forming load of 12000-20000 N, maintain the load for 3-5.5 h, and control the total compressive strain to be 70%-80%; remove the load, and then cool to room temperature with the furnace, and take out the creep-formed sample, i.e., the β-solidifying γ-TiAl alloy sample; 5. Determine the heat treatment temperature: Use differential scanning calorimetry to analyze the β-solidified γ-TiAl alloy sample obtained in step 4 and measure the α phase transformation temperature T α ; 6. Heat treatment: Place the β-solidified γ-TiAl alloy sample after creep forming in step 4 into a heat treatment furnace and then perform step-by-step heating: uniformly heat to 500-550 °C at a rate of 12-18 °C / min and hold for 2-8 min; then uniformly heat to the target temperature (T at a rate of 12-16 °C / min). α -30)℃~(T α -10) ℃, keep it for 10-30 min; cool it to room temperature with the furnace, and then obtain the final sample, that is, the β-solidifying γ-TiAl alloy with a dual-state structure with layered distribution characteristics, and the preparation is completed.
2. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 1: Ultrasonic cleaning using anhydrous ethanol.
3. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that In step 1, the purity of the pure Ti rod is greater than 99.9%, the purity of the sponge Ti particles is greater than 99.9%, the purity of the high-purity Al block is greater than 99.9%, the Nb content in the Al-Nb intermediate alloy particles is 53.7 wt.%, the Mo content in the Al-Mo intermediate alloy particles is 50.5 wt.%, and the purity of the pure B powder is greater than 99.9%.
4. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that In step 1, 4-6% of the Al element mass is added during weighing to compensate for the volatilization of the Al element during the smelting process.
5. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 4: Use 200#~3000# sandpaper to polish the surface.
6. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 4: The material of the pressure head is nickel-based high-temperature alloy.
7. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 4: Control the temperature fluctuation range during the forming process to -1~1°C.
8. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 4: Apply a preload of 450~900N.
9. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that The size of the cylinder in step 4 is Ф8 mm × 12 mm.
10. The method for preparing a β-solidifying γ-TiAl alloy having a dual-state structure with a layered distribution characteristic according to claim 1, characterized in that Step 4: ultrasonic cleaning with anhydrous ethanol.